Quality of life and mental health of Dentistry students during COVID-19 pandemic (Research, Society and Development, 2022)
Objective: To analyze the quality of life and mental health of students at the Federal University of Uberlândia during the COVID-19 pandemic, identifying levels of depression, anxiety, stress and psychological well-being. Methodology: Students regularly enrolled in the UFU Dentistry course in the years 2020 and 2021 were included who answered three online questionnaires: socio-demographic profile, Anxiety, Stress and Depression Scale (DASS-21) and Psychological Well-Being Scale (PGWB). Data were analyzed with Mann Whitney and Kruskal-Wallis tests. Results and Discussion: 268 students participated, 74% of which were women, between 18 and 23 years old (72.3%), who suffered financial impact (69%) and change in their daily routine (42.7% in 2020 and 54.6 % in 2021) with the pandemic. Most students had normal levels of Anxiety, Stress and Depression and average levels of Psychological Well-Being in both years. Women had higher levels of anxiety, stress and depression and lower Psychological Well-being in the year 2021. Students in the final periods (8 to 10) had a higher level of anxiety in 2020, while those in the initial periods had the highest level of Well-being. Being, General Health and Self-Control in 2021. Students in the final periods (8 to 10) had a higher level of anxiety in 2020, while those in the initial periods had the highest level of Well-Being, General Health and Self-Control in 2021. Conclusion: The Covid-19 pandemic has affected UFU Dentistry students in a different way, being more harmful to the quality of life and mental health of women and of the last periods of the course (8 to 10).